2009
DOI: 10.1111/j.1365-2249.2009.03898.x
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance between T helper type 17 and T regulatory cells in patients with primary biliary cirrhosis: the serum cytokine profile and peripheral cell population

Abstract: SummaryPrimary biliary cirrhosis (PBC) is an organ-specific autoimmune liver disease characterized by progressive loss of intrahepatic small bile ducts. Cellular immune mechanisms involving T cell reaction are thought to be involved significantly in the pathogenesis of PBC. Recent studies have independently revealed enhanced T helper type 17 (Th17) response and weakened T regulatory cell (Treg) response in some autoimmune diseases, indicating a role of Th17/Treg imbalance in the pathogenesis of autoimmunity. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
117
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(122 citation statements)
references
References 45 publications
4
117
0
1
Order By: Relevance
“…The plasma TGF-β concentration in patients with early-stage PBC was lower than the concentration in healthy individuals, consistent with the Th17-Treg imbalance in PBC. However, the concentration was higher in patients with late-stage PBC than in healthy individuals, a result that seems to be different from those of Rong et al (2009). Previous studies showed that TGF-β and IL-6 expression levels are elevated in the fibrotic process in PBC, whereas the inflammatory process involves decreased TGF-β and increased Th17 expression levels (Fenoglio et al 2012).…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…The plasma TGF-β concentration in patients with early-stage PBC was lower than the concentration in healthy individuals, consistent with the Th17-Treg imbalance in PBC. However, the concentration was higher in patients with late-stage PBC than in healthy individuals, a result that seems to be different from those of Rong et al (2009). Previous studies showed that TGF-β and IL-6 expression levels are elevated in the fibrotic process in PBC, whereas the inflammatory process involves decreased TGF-β and increased Th17 expression levels (Fenoglio et al 2012).…”
Section: Discussionmentioning
confidence: 82%
“…Patients with PBC showed below-normal numbers of circulating CD4+CD25 high Tregs (Wang et al 2010;Wang et al 2015b), and UDCA treatment for 1 year increased these numbers (Lacerda et al 1995). Rong et al (2009) reported increased IL-23 and IL-6 and decreased TGF-β concentrations in the circulation of patients with PBC. Taken together, these findings highlight the activation of Th17 and inhibition of Tregs in PBC (Rong et al 2009).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…CD4 T-cell responses play a critical role in the resolution of infection and impaired HCV-specific CD4 Tcell responses are observed in chronic HCV [6] . Interleukin (IL)-17-producing T-helper (Th)17 cells have been reported to trigger tissue inflammation and damage [7] and there is accumulating evidence that Th17 cells are important contributors to hepatic inflammation and liver cirrhosis [8] . Th17 cells and its signature cytokine, interleukin-17 (IL-17), have been found increased frequencies within certain tumors .…”
Section: Introductionmentioning
confidence: 99%